Different Transmission Dynamics of Coronavirus Disease 2019 (COVID-19) and Influenza Suggest the Relative Efficiency of Isolation/Quarantine and Social Distancing Against COVID-19 in China. (20th October 2020) - Lei, Hao; Wu, Xifeng; Wang, Xiao; Xu, Modi; Xie, Yu; Du, Xiangjun; Cowling, Benjamin J; Li, Yuguo; Shu, Yuelong
Abstract: Background: Nonpharmaceutical interventions (NPIs) against coronavirus disease 2019 (COVID-19) are vital to reducing transmission risks. However, the relative efficiency of social distancing against COVID-19 remains controversial, since social distancing and isolation/quarantine were implemented almost at the same time in China. Methods: In this study, surveillance data of COVID-19 and seasonal influenza in 2018–2020 were used to quantify the relative efficiency of NPIs against COVID-19 in China, since isolation/quarantine was not used for the influenza epidemics. Given that the relative age-dependent susceptibility to influenza and COVID-19 may vary, an age-structured susceptible/infected/recovered model was built to explore the efficiency of social distancing against COVID-19 under different population susceptibility scenarios. Results: The mean effective reproductive number, R t, of COVID-19 before NPIs was 2.12 (95% confidence interval [CI], 2.02–2.21). By 11 March 2020, the overall reduction in R t of COVID-19 was 66.1% (95% CI, 60.1–71.2%). In the epidemiological year 2019–20, influenza transmissibility was reduced by 34.6% (95% CI, 31.3–38.2%) compared with transmissibility in epidemiological year 2018–19. Under the observed contact pattern changes in China, social distancing had similar efficiency against COVID-19 in 3 different scenarios. By assuming the same efficiency of social distancing against seasonal influenza and COVID-19 transmission, isolation/quarantine and social distancing could lead to 48.1% (95% CI, 35.4–58.1%) and 34.6% (95% CI, 31.3–38.2%) reductions of the transmissibility of COVID-19, respectively. Conclusions: Though isolation/quarantine is more effective than social distancing, given that the typical basic reproductive number of COVID-19 is 2–3, isolation/quarantine alone could not contain the COVID-19 pandemic effectively in China. Abstract : In a comparative study of the transmission dynamics of seasonal influenza and coronavirus disease 2019 (COVID-19) in China, we evaluated the efficiency of isolation/quarantine and social distancing against transmission, and found that isolation/quarantine alone could not contain COVID-19 effectively.